P1.018 Analysis of Mosaic Penicillin-Binding Protein 2 Variants with Ala501 Mutations That Confer High-Level Resistance to Expanded-Spectrum Cephalosporins in Neisseria Gonorrhoeae. (13th July 2013) - Tomberg, J; Unemo, M; Davies, C; Nicholas, R
Abstract : Decreased susceptibility to the expanded-spectrum cephalosporins cefixime and ceftriaxone in Neisseria gonorrhoeae has increased dramatically over the past decade globally and recently resistance was reported to the last remaining recommended treatment option, ceftriaxone, raising fears that gonorrhoea may become untreatable. The major reason for decreased susceptibility has been mosaic penA alleles encoding penicillin-binding protein 2 (PBP2), the major target for these antibiotics, with up to 70 mutations relative to wild-type. Less prevalent in most settings has been non-mosaic penA alleles containing A501V or A501T mutations just downstream of the KTG active site motif that also confer decreased susceptibility. We have shown that Ala501 mutations, when introduced into mosaic penA alleles, confer resistance to expanded-spectrum cephalosporins, and recently, a novel mosaic penA allele containing an A501P mutation and resulting in ceftriaxone resistance was described. To understand the role of Ala501 mutations in mosaic penA alleles, we transformed FA19 with the mosaic penA allele from 35/02 harbouring a randomised codon at position 501 and selected for increased cefixime resistance. From this screen, we identified five Ala501 mutations (Val, Thr, Ser, Pro and Arg) that resulted in increased cefixime resistance, indicating that only a small subset of mutations are capable of conferring resistance. Surprisingly, only one clone with an A501P mutation was selected, perhaps suggesting a fitness defect with this mutation. MIC analyses showed that mutation of Ala501 to Val, Ser or Thr conferred ∼2.5-fold increases in resistance, whereas mutation to Arg and Pro increased resistance nearly 5-fold. PBP2–6140CT (PBP2 containing four C-terminal mutations) harbouring A501V or A501T mutations was crystallised and revealed major ordering and some reorganisation of the β3-β4 hairpin that is immediately adjacent to the active site. Modeling of β-lactams into the crystal structure indicates that the mutations likely introduce a steric clash with the R1 substituent of expanded-spectrum cephalosporins.